ANALISIS KINERJA KEUANGAN SERBA USAHA BERBASIS PERMENKOP UKM NO.6 TAHUN 2016 - Dumais , Bianca Anastasiya; Nurhayati Nafsiah, Siti (Catholic University Musi Charitas, 2024)
This study aims to analyze the financial performance of the Patra Palembang Employee Cooperative for the 2019-2022 period based on the regulation of the Deputy for Supervision of the Ministry of Cooperatives and SMEs Number. 06/Per/Dep.6/IV/2016. The results of this study indicate that the capital aspect obtains a score of 85.00, thus obtaining a healthy predicate; aspects of earning asset quality get a score of 81.23, thus getting the title of healthy; aspects of management get a score of 90.00, thus getting a healthy predicate; the efficiency aspect gets a score of 100.00, so that it gets a healthy predicate; the liquidity aspect gets a score of 66.66, so that it gets the title of being under supervision; aspects of independence and growth get a score of 100, thus getting the title of healthy; aspects of identity get a score of 81.3, thus getting a healthy predicate. Overall, the financial performance of the Patra Palembang Employee Cooperative for the 2019-2022 period received an average score of 75.63 so it is in the fairly healthy category.